PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK BITTERSWEET BY NAJLA DENGAN KEPUASAN KOSUMEN SEBAGAI VARIABEL MEDIASI - Arya Yudha Pratama; Wiyadi Wiyadi (JURNAL LENTERA BISNIS, 2024)
The research was conducted by measuring the influence that product price and quality have on purchasing decisions by paying attention to consumer satisfaction as a mediating variable. Furthermore, bittersweet by Najla was chosen as the research object because of its popularity. Through the purposive sampling method, measurements using quantitative methods were obtained by distributing questionnaires to consumers of Bittersweet Najla who are 15 years old, as well as people who like sweet foods, so a total of 175 respondents were obtained. The findings show that customer satisfaction and price and product quality influence purchasing decisions, not only a direct influence but also a mediating influence on consumer satisfaction which also has a significant impact on the relationship between price and product quality on purchasing decisions. Key words: Price, Product Quality, Purchasing Decisions, Consumer Satisfaction